Peran Edukasi Literasi Keuangan dalam Mengatasi Budaya Berhutang dan Gagal Bayar pada Pinjaman Online - Naela Farkhati; Syifa Rasyiqa; Rudi Sanjaya (International Forum of Researchers and Lecturers, 2024)
The phenomenon of online loans has increased significantly in Indonesia, presenting its own challenges for the community in terms of financial management. One of the impacts of the rise of online loans is the emergence of an unhealthy debt culture, where many people are trapped in a debt pattern that is difficult to control, leading to default. This study aims to examine the role of financial literacy as an important factor in overcoming the culture of excessive debt and reducing the number of defaults on online loans. The method used in this study is a literature review that focuses on data from other relevant document sources and those that use online loan services. The results of the study show that financial literacy education can provide the community with a better understanding of financial risks and responsibilities, as well as encourage wiser behavior in making financial decisions.